Struktur Wacana dan Pesan Dakwah pada Lagu Lawlaka Maher Zaen - Hendro Eko Setiawan; Ziana Walidah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
The purpose of this paper is to describe the structure that exists in the lyrics of the song Lawlaka so that readers especially song lovers can know, understand and know what is contained in the song lyrics Lawlaka as well as the linguistic aspects in it. The primary data is the Lawlaka text contained in the Youtube Awkening Music channel, while the secondary data uses Van Dijk's discourse analysis. The results show that there is a complex structure found in the lyrics of the song Lawlaka. In the text dimension it contains micro and macro structures: from the micro structure it contains the thematic elements of the hope of His grace, begging for forgiveness and praise. The superstructure that contains the schematic shows the title / lead. In the macro structure there are background elements, details and meanings. Whereas the social dimension of the Lawlaka song is not just textual but has meaning within it. As for the social context of his sinful state that others feel. Maher Zaen composed the song in reference to his words and hadith of the prophet Muhammad SAW for the public awareness of the importance of the mercy of Allah SWT. the message of the preaching contained: inviting man to return to the path of Allah SWT as written in the hadith and the word of Allah SWT. IntisariTujuan tulisan ini ialah untuk mendeskripsikan struktur yang ada dalam lirik lagu Lawlaka sehingga pembaca khususnya penikmat lagu dapat mengetahui, memahami dan mengetahui apa yang terkandung dalam lirik lagu Lawlaka serta aspek-aspek kebahasaan didalamnya. Adapun data primer adalah teks Lawlaka yang ada didalam chanel Youtube Awkening Music, sedangkan data skunder menggunakan analisis wacana Van Dijk. Hasil penelitian menunjukan bahwa adanya struktur kompleks yang terdapat dalam lirik lagu Lawlaka. Pada dimensi teks memuat struktur mikro dan makro: dari struktur mikro memuat unsur tematik tentang pengharapan rahmat-Nya, memohon ampun dan pujian. Adapun superstruktur yang memuat skematik menunjukan adanya judul/lead. Pada struktur makro terdapat adanya elemen latar, detail dan maksud. Sedangkan pada dimensi sosial lagu Lawlaka tidak hanya sebatas teks saja namun ada makna yang terkandung didalamnya. Adapun dalam konteks sosial berkenaan dengan keadaan dirinya yang merasa penuh dosa yang juga dirasakan oleh orang lain. Maher Zaen mencipta lagu tersebut merujuk pada firman-Nya dan hadits nabi Muhammad SAW untuk kesadaran masyarakat akan pentingnya rahmat Allah SWT. pesan dakwah yang terkandung: mengajak manusia kembali ke jalan Allah SWT sebagaimana tertulis dalam hadis rosul dan firman Allah SWT.